SYPHILIS AND HIV INFECTION: PROZONE EFFECT IN A PATIENT WITH NEUROSYPHILIS - Slaibi, Érica Bertolace (2013)
We report a case of prolonged secondary syphilis with asymptomatic neurological involvement in HIV- -infected patient. A 26-year-old male patient who was diagnosed three years earlier with HIV infection presented with skin lesions on the feet and hands, alopecia, fever, arthralgia, weight loss of 8 Kg which began one year before and had a negative VDRL. During hospitalization, his VDRL was 1:1024 and a CSF-VDRL positive. The patient had an excel- lent clinical response to treatment with crystalline penicillin. The syphilis diagnosis should be considered in HIV-infected patients with severe clinical disease, even when the VDRL is negative. KEYWORDS – Sexually transmitted diseases; HIV infections; Neurosyphilis; Syphilis.